ENVIRONMENTAL ACCOUNTING ON FINANCIAL PERFORMANCE AND REPUTATION OF MINING COMPANY IN INDONESIA - Najihah, Naila; Indriastuti, Maya (TRIKONOMIKA, 2020)
This research analyzes and tests empirically on how environmental accounting application can improve the company’s performance and reputation. The company has a strategic role in the development of national economy. They are not only contributing to the economic growth in Indonesia but also absorb the workforce in large quantities. The population in this research is all manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Samples determined using purposive sampling, which are active mining companies on the Indonesia Stock Exchange in 2016-2018. From this sampling method, the final samples used in this research are 60 firm year samples (20 companies x 3 years). The data used is secondary data and had analyzed using simple regression analysis. The results show that the implementation of environmental accounting gives positive impact on financial performance and company reputation. The increasing quality of financial performance and intrinsic reputation is established by the presence of environmental quality and social responsibility undertaken by the company.